Complications of Percutaneous Peritoneal Dialysis Catheter - Oza-Gajera, Bharvi P.; Abdel-Aal, Ahmed K.; Almehmi, Ammar (Seminars in Interventional Radiology, 2022)
A functional peritoneal dialysis (PD) catheter is the cornerstone for the success of renal replacement therapy. This success is largely dependent on adhering to best practices during catheter insertion, which starts with a comprehensive preoperative evaluation that helps in determining the catheter configuration type and both entry and exit sites. Additionally, following the best practice guidelines during PD catheter insertion minimizes undesirable complications and provides a durable functional access for dialysis. However, adverse complications are still encountered despite abiding with these clinical guidelines. These complications are categorized into mechanical and infectious groups. The description and management of these adverse events are discussed in detail in this article with particular attention to the technical pitfalls that can occur during catheter insertion. Avoiding these pitfalls can minimize PD catheter complications and potentially improve clinical outcomes.
Keywords: peritoneal dialysis; peritonitis; infectious complications; dialysis access; peritoneal dialysis catheter; interventional radiology